2023
DOI: 10.1021/acscatal.3c03497
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Nucleophilic Site Enables Expedient Synthesis of CF3-Containing Thiazoles and Allenes from 1,3-Enynes

Xiangyu Li,
Na Li,
Lan Yang
et al.

Abstract: Typically, trimethylsilyl isothiocyanate (TMSNCS) is used as a nucleophilic thiocyanate building block ( − S−C�N) that reacts with various electrophiles. However, it has been less explored as a source of isothiocyanates ( − N�C�S), which can usually be converted by thermal isomerization of allyl or propargyl thiocyanates. Achieving a method with precise site control is even more challenging. Here, we demonstrate an approach that uses metal catalysts to control switchable nucleophilic sites and provide a strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This selectivity is dependent on the enone substrate, but the NCS isomer could be easily purified by column chromatography. This reactivity represents one of the few examples where TMSNCS is reported as a reagent for the formation of isothiocyanates (–NCS), 40–44 while there are many examples of its use to form thiocyanates (–SCN). 45–47 First, we checked the electronic effects of the aromatic substituents and found that enones with electron-donating (Me, OMe) and electron-withdrawing (CN, F, CF 3 , NO 2 ) groups at the para position of the phenyl ring were well-tolerated, giving the desired isothiocyanato products ( 2b–2g ) in excellent yields (87–94%).…”
Section: Resultsmentioning
confidence: 99%
“…This selectivity is dependent on the enone substrate, but the NCS isomer could be easily purified by column chromatography. This reactivity represents one of the few examples where TMSNCS is reported as a reagent for the formation of isothiocyanates (–NCS), 40–44 while there are many examples of its use to form thiocyanates (–SCN). 45–47 First, we checked the electronic effects of the aromatic substituents and found that enones with electron-donating (Me, OMe) and electron-withdrawing (CN, F, CF 3 , NO 2 ) groups at the para position of the phenyl ring were well-tolerated, giving the desired isothiocyanato products ( 2b–2g ) in excellent yields (87–94%).…”
Section: Resultsmentioning
confidence: 99%
“…They are also versatile synthons which could be converted with ease to other sulfur-containing molecules such as thiols, thioethers, carbamothioates, thiotetrazole, perfluoromethylsulfanes and phosphinothioates. [23] Over the past decades, a wide range of methodologies have been developed to construct organic thiocyanates using an N-SCN agent, [24] TMSSCN [25] or KSCN, [26][27][28][29][30][31][32][33][34] or through sulfur cyanation. [35] The inexpensive and benchtop-stable KSCN is a particularly versatile thiocyanating agent, which might undergo a nucleophilic, [26][27][28][29] electrophilic [30,31] or radical coupling [32][33][34] under the conditions of an oxidant, [26,30,32] visible-light irradiation [27,33] or electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The trifluoromethyl (CF 3 ) group functions as an excellent bioisostere of the methyl group in medicinal chemistry and can improve the metabolic stability, bioavailability, and cellular membrane permeability of molecules. 7 Thus, introducing trifluoromethyl groups into molecular skeletons is of great importance. Among many trifluoromethyl substituents, trifluoromethyl-containing allene skeletons are preferred because of their good plasticity.…”
Section: Introductionmentioning
confidence: 99%